Fighting terrorism in Africa when existing terrorism levels matter - Simplice Asongu; Vanessa Tchamyou; Ndemaze Asongu; Nina P. Tchamyou (African Governance and Development Institute (AGDI), 2019)
This study examines policy tools in the fight against terrorism when existing levels of terrorism matter in 53 African countries for the period 1998-2012. The empirical evidence is based on contemporary, non-contemporary and Instrumental Variable Quantile regressions (QR) which enable the investigation throughout the conditional distributions of domestic, transnational and total terrorism dynamics. The following findings are established. First, counterterrorism policy instruments of inclusive human development and military expenditure further fuel terrorim. Second, political stability negatively affects terrorism with a negative threshold effect. Political stability estimates are consistently significant with increasing negative magnitudes throughout the conditional distributions of domestic and total terrorism. Policy implications are discussed.
Keywords: C52; D74; F42; O16; O38; 330; Terrorism; Inclusive development; Political stability; Military expenditure; Africa